76.5k views
0 votes
Please answer the two questions!

Please answer the two questions!-example-1
User Emonigma
by
5.1k points

1 Answer

5 votes

Given:

The expressions are

(c)
\left\{\left((2^4* 3^6)/(12^2)\right)^0\right\}^3

(d)
\frac{13^3* 7^0}{\{(65* 49)^2\}^1}

To find:

The simplified form of the given expression.

Solution:

(c)

We have,


\left\{\left((2^4* 3^6)/(12^2)\right)^0\right\}^3

We know that, zero to the power of a non-zero number is always 1. So,
\left((2^4* 3^6)/(12^2)\right)^0=1


\left\{\left((2^4* 3^6)/(12^2)\right)^0\right\}^3=(1)^3


\left\{\left((2^4* 3^6)/(12^2)\right)^0\right\}^3=1

Therefore, the value of the given expression is 1.

(d)

We have,


\frac{13^3* 7^0}{\{(65* 49)^2\}^1}

It can be written as


\frac{13^3* 7^0}{\{(65* 49)^2\}^1}=(13^3* 1)/((65* 49)^2)


\frac{13^3* 7^0}{\{(65* 49)^2\}^1}=(13* 13* 13)/((65* 49)(65* 49))


\frac{13^3* 7^0}{\{(65* 49)^2\}^1}=(13)/((5* 49)(5* 49))


\frac{13^3* 7^0}{\{(65* 49)^2\}^1}=(13)/(60025)


\frac{13^3* 7^0}{\{(65* 49)^2\}^1}=(13)/(60025)

Therefore, the value of given expression is
(13)/(60025).

User Petro
by
5.3k points